2006
DOI: 10.1177/0269215506070805
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a health promotion education programme for people with multiple sclerosis

Abstract: The OPTIMISE programme produced significant changes in health-promoting behaviours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
105
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(110 citation statements)
references
References 19 publications
5
105
0
Order By: Relevance
“…This study proposes informational support can indirectly improve health outcomes in participants through improved adherence to interventions. This is supported by past literature, which found signi icant associations between informational support and health promotion with consequential increases in physical activity [19] and there are a number of reasons as to why this could be. Methley [21], highlighted the bene its of timely information delivery on participants' emotional wellbeing.…”
Section: Benefi Ts Attributable To Social Supportsupporting
confidence: 82%
See 1 more Smart Citation
“…This study proposes informational support can indirectly improve health outcomes in participants through improved adherence to interventions. This is supported by past literature, which found signi icant associations between informational support and health promotion with consequential increases in physical activity [19] and there are a number of reasons as to why this could be. Methley [21], highlighted the bene its of timely information delivery on participants' emotional wellbeing.…”
Section: Benefi Ts Attributable To Social Supportsupporting
confidence: 82%
“…Particular techniques like health coaching and motivational interviewing can enhance adherence to rehabilitation interventions. The delivery of timely and accurate informational support can improve emotional well-being and increase physical activity [19][20][21]. Literature has highlighted the indirect, positive effect that social support has on physical activity in MS participants, through increasing levels of self-ef icacy [22,23].…”
Section: Social Supportmentioning
confidence: 99%
“…However, research evaluating the use of multiple interventions to reduce the impact of these environmental factors on MS-related symptoms is sparse. The OPTIMISE study 25 used a multidisciplinary program to encourage health-promoting activities such as physical activity, fatigue and stress management, and nutritional awareness over a period of 8 weeks, which led to significant increases in healthy activities by MS subjects (e.g., the number of subjects performing leisure-time physical activity increased from 6% at baseline to 40% after the program).…”
Section: Discussionmentioning
confidence: 99%
“…25 In a similar study of health-behavior promotion, a 5-day residential retreat aimed at promoting lifestyle modification (diet, exercise, and stress-reducing activities) was conducted and demonstrated significant improvement in health-related quality of life at 1 and 5 years. 26 However, adherence of subjects to the intervention was not evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Group healthpromotion programmes aimed at increasing knowledge, skills, and confidence have been explored in the literature; studies have indicated that these programmes, which consist of, for example, 8 weekly sessions 1.5 hours in duration, are effective in increasing the frequency of health-promoting activities, selfefficacy for health behaviours, and selected aspects of QoL. 4,5 …”
mentioning
confidence: 99%